2014
DOI: 10.1021/bc500467u
|View full text |Cite
|
Sign up to set email alerts
|

Effective Targeting of DC-SIGN by α-Fucosylamide Functionalized Gold Nanoparticles

Abstract: Abstract:Dendritic Cells (DCs), the most potent antigen-presenting cells, play a critical role in the detection of invading pathogens, which are recognized also by multiple carbohydrate-specific receptors.Among them, DC-SIGN is one of the best characterized, with high-mannose and Lewis-type glycan specifity. In this study, we present a potent DC-SIGN targeting device developed using gold nanoparticles functionalized with α-fucosyl-β-alanyl amide. The nanoparticles bound to cellular DC-SIGN and induced internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…Targeting ligands [56][57][58][59][60] may be modified onto the AuNP surface to specifically deliver therapeutic cargos into tissues and organs. Recently, tumor-targeted mesoporous silicaencapsulated GNRs (GNRs@mSiO 2 ) for chemotherapy and photothermal therapy (PTT) have been developed by Shen et al 61 In this study, RGD peptides, a targeting ligand for α v β 3 integrin receptors that are known to overexpress on several cancer cells, were conjugated to the terminal groups of PEG on GNRs@mSiO 2 (namely, pGNRs@mSiO 2 -RGD).…”
Section: Surface Functionalization Of Aunpsmentioning
confidence: 99%
“…Targeting ligands [56][57][58][59][60] may be modified onto the AuNP surface to specifically deliver therapeutic cargos into tissues and organs. Recently, tumor-targeted mesoporous silicaencapsulated GNRs (GNRs@mSiO 2 ) for chemotherapy and photothermal therapy (PTT) have been developed by Shen et al 61 In this study, RGD peptides, a targeting ligand for α v β 3 integrin receptors that are known to overexpress on several cancer cells, were conjugated to the terminal groups of PEG on GNRs@mSiO 2 (namely, pGNRs@mSiO 2 -RGD).…”
Section: Surface Functionalization Of Aunpsmentioning
confidence: 99%
“…These AuNPs induced pro-inflammation of MDDCs, as well as CD80, CD86, and HLA-DR upregulation. In addition, Arosio et al 39 synthesized AuNPs functionalized with α-fucosylamide, a molecule which facilitated DC-SIGN receptor targeting. These AuNPs were internalized by MDDCs via the DC-SIGN receptor without triggering immune responses, thus they can be utilized for delivery purposes.…”
Section: 23mentioning
confidence: 99%
“…Ara h 1, Der p 1, Der p 2, Can f 1 and Cyn d 1 (Bermuda grass pollen) have been reported as ligands for DC-SIGN and/or DC-SIGNR [41,42]. DC-SIGN has been suggested to modulate human DC activation for Th1 cell polarization, or IL-10-mediated regulatory responses [40,43,44]. Interestingly, Furmonaviciene et al [45] showed that Der p 1 cleaves DC-SIGN and DC-SIGNR by its proteolytic activity and releases these receptors from the cell surface in human DCs, thereby promoting Th2 cell polarization.…”
Section: C-type Lectinsmentioning
confidence: 99%